2023
DOI: 10.3390/genes14020343
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Identification, Evolutionary and Functional Analyses of WRKY Family Members in Ginkgo biloba

Abstract: WRKY transcription factors (TFs) are one of the largest families in plants which play essential roles in plant growth and stress response. Ginkgo biloba is a living fossil that has remained essentially unchanged for more than 200 million years, and now has become widespread worldwide due to the medicinal active ingredients in its leaves. Here, 37 WRKY genes were identified, which were distributed randomly in nine chromosomes of G. biloba. Results of the phylogenetic analysis indicated that the GbWRKY could be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 86 publications
0
2
0
Order By: Relevance
“…Previous studies have identified variants of the conserved WRKYGQK motif in multiple species. Two variants (WKKYGKK and WKKYGEK) have been reported for Taraxacum kok-saghyz [ 39 ], while Ginkgo biloba has four variants: WRKYAQK, WRKYGEK, WRKYGRK, and WRKYGKK [ 40 ]. Moreover, three variants have been observed in Kandelia obovata (WRKYGEK, WRKYGKK, and WRKYGQK) [ 41 ] and one in Cannabis sativa (WRKYGKK) [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have identified variants of the conserved WRKYGQK motif in multiple species. Two variants (WKKYGKK and WKKYGEK) have been reported for Taraxacum kok-saghyz [ 39 ], while Ginkgo biloba has four variants: WRKYAQK, WRKYGEK, WRKYGRK, and WRKYGKK [ 40 ]. Moreover, three variants have been observed in Kandelia obovata (WRKYGEK, WRKYGKK, and WRKYGQK) [ 41 ] and one in Cannabis sativa (WRKYGKK) [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have identi ed variants of the conserved WRKYGQK motif in multiple species. Two variants (WKKYGKK and WKKYGEK) have been reported for Taraxacum kok-saghyz [39], while Ginkgo biloba has four variants: WRKYAQK, WRKYGEK, WRKYGRK, and WRKYGKK [40]. Moreover, three variants have been observed in Kandelia obovata (WRKYGEK, WRKYGKK, and WRKYGQK) [41] and one in Cannabis sativa (WRKYGKK) [42].…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have focused on the tolerance of G. biloba. With the release of the ginkgo genome sequence, more gene families associated with resistance traits in G. biloba are being revealed [15,16]. However, information on the NF-Y family in G. biloba remains scarce.…”
Section: Introductionmentioning
confidence: 99%